Evolutionary insights into Interleukin-12 family targets across 405 species - Wang, Weibin; Li, Dawei; Luo, Kaiyong; Chen, Baozheng; Li, Xuzhen; Hao, Tingting; Guo, Dazhong; Dong, Yang; Ning, Ya (Frontiers in Immunology, 2025)
The Interleukin-12 (IL-12) family ligand subunits (IL-12s) and receptor subunits (IL-12Rs) constitute pivotal regulators of immune homeostasis, with direct implications in autoimmune pathologies and oncogenesis. Through phylogenetic reconstruction, synteny analysis, and sequence alignment across 400+ animal species, we delineated the evolutionary trajectories and functional diversification of these immune mediators. Phylogenetic analysis revealed IL-12Rs originated prior to the mollusk era (514-686.2 million years ago, Mya), while ligand subunits p19/p28 emerged during the mammalian and avian epoch (180-225 Mya). Structural characterization identified three evolutionarily invariant signature motifs within the fibronectin type III (fn3) domain essential for receptor-ligand interface stability. Furthermore, phylogenetically ultra-conserved residue and motif configurations were mapped, revealing candidate therapeutic epitopes. These findings establish an evolutionary framework explaining functional conservation/divergence in IL-12 signaling components. The identified ancient receptor architectures coupled with derived ligand innovations provide a blueprint for cross-species immunotherapy design targeting conserved interaction interfaces. The conserved molecular signatures offer dual utility in developing precision therapies and interspecies disease management strategies, particularly for translational applications across human medicine, agriculture, and aquaculture.